Blood sample as a promising diagnostic tool in oncology - literature review - Drobek, Dominik; Wojtala, Kacper; Turek, Michał; Winiarz, Aleksandra; Szlendak, Paula; Toś, Katarzyna; Wąsala, Katarzyna; Grosman, Sylwia; Węgrzyniak, Agata; Wokurka, Wojciech (Journal of Education, Health and Sport, 2023)
Introduction Cancer is one of the leading causes of death worldwide. The molecular characterization of solid tumors has provided significant advances in oncology, and genome profiling using circulating tumor DNA (ctDNA) has helped improve the quality of medical care for patients with cancer. Liquid biopsy is a diagnostic molecular test to demonstrate the presence of circulating tumor DNA or circulating tumor cells released from primary or metastatic solid tumors. In addition, the minimally invasive nature of the liquid biopsy enables quick verification of the grade of malignancy. Observation of ctDNA in blood tests is of great importance at the treatment stage, it allows to determine resistance to the applied treatment, response to therapy and to predict relapse before it occurs. Aim of the study The aim of this review is to present information on the use of circulating tumor DNA together with circulating tumor cells in oncological diagnostics. Materials and methods The work was created based on the PubMed database. Articles were searched in English using the following keywords: ctDNA, CTC, cfDNA. Results Currently, ctDNA analysis is an alternative to traditional molecular diagnostics of cancer tissue, assessment of the effectiveness of therapy, monitoring of tumor dynamics, monitoring of progression and predicting recurrence. Summary There are not many diagnostic methods for detecting ctDNA. Due to the short length of the fragments and the low content in the samples, ctDNA analysis requires more sensitive techniques to ensure its reliability compared to methods used in solid tissue biopsies. Existing techniques of ctDNA analysis focus mainly on the identification of mutations in advanced stages of cancer, less often on early diagnosis.